2018
DOI: 10.1177/0363546518786970
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver and Intraobserver Reliability of an MRI-Based Classification System for Injuries to the Ulnar Collateral Ligament

Abstract: The newly proposed 6-stage MRI-based classification utilizing grade and location of the injury had substantial to near perfect agreement among and within fellowship-trained observers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Higher grade UCL tearing often results in valgus instability of the elbow, a career-threatening injury to throwing athletes that often requires surgery, especially in distal and complete tears (►Table 1). 31 Handball field players are at risk for this injury complex but to a lesser degree than baseball pitchers. Reasons may include differences in biomechanics and lower degrees of elbow flexion during throwing.…”
Section: Elbowmentioning
confidence: 99%
“…Higher grade UCL tearing often results in valgus instability of the elbow, a career-threatening injury to throwing athletes that often requires surgery, especially in distal and complete tears (►Table 1). 31 Handball field players are at risk for this injury complex but to a lesser degree than baseball pitchers. Reasons may include differences in biomechanics and lower degrees of elbow flexion during throwing.…”
Section: Elbowmentioning
confidence: 99%
“…In this study, a previously proposed 6-stage MRI-based classification system with high intraobserver and interobserver reliability, accounting for location and severity of UCL tears, was found to carry clinical decision-making value for both the general population and baseball players alike. 6,23 UCL tears in both general athletes and baseball players, regardless of position, were found to more frequently fail nonoperative management, despite a specialized rest and rehabilitation program if the tear was distal (stage 3) and complete (substage B). For baseball players specifically, distal tears were 36 times more likely and complete tears 7 times more likely to fail nonoperative management and require surgery.…”
Section: Discussionmentioning
confidence: 97%
“…These authors found that 9 of 11 patients who failed nonoperative management had distal tears, and 17 of 21 who did not fail had proximal tears, suggesting that location may play a role in treatment decision making. Ramkumar et al 23 introduced an MRI-based classification system that accounted for both tear location and severity (Table 1), which demonstrated high intraobserver and interobserver reliability among 9 readers across multiple institutions.…”
mentioning
confidence: 99%
“…Greater attention is being paid to the grade, anatomic location, and completeness of UCL injury, as demonstrated by 3 recently proposed MR-based classification schemes (Table 2). 25,29,30…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that partial injuries occurring in different anatomic locations may behave differently and that some may be amenable to nonoperative management. 15,16,19,21,[29][30][31][32] Unfortunately, uniform consensus has not yet been achieved regarding what tear locations result in the greatest instability or poorest outcomes with nonsurgical treatment. The purpose of this study was to determine the amount of ulnohumeral joint space gapping measured using stress ultrasound with applied valgus stress that occurs with clinically relevant partial tears of the UCL in a cadaveric model as compared with that of the intact and completely torn states.…”
mentioning
confidence: 99%